Baclofen and Clonazepam Overdose in a Patient with Chronic Neck and Shoulder Pain - Ehler, Edvard; Prax, Tomáš; Meleková, Alena; Štětkářová, Ivana (My University, 2017)
Baclofen, a derivative of gama-aminobutyric acid, is used for symptomatic relief of skeletal muscle spasms and spasticity, particularly in patients with multiple sclerosis. Most published cases of baclofen overdose include acute intentional overdose or intoxication in the context of spasmolytic treatment. The effects of baclofen overdosage may cover a broad variety of clinical manifestations including coma, muscle flaccidity, seizures, severe respirátory depression with need for mechanical ventilation, autonomic disturbances with abnormal heart rate (either bradycardia or tachycardia), hypo- or hypertension, and either miosis or mydriasis. We report a 42-year-old man who was found with generalized convulsive seizures and referred in state of deep coma. Toxicological analysis of blood and urine disclosed clonazepam and a high level of baclofen. Only with oxygen inhalation and supportive diuretic therapy he regain consioussness after 28 hours.
Předávkování baklofenem a klonazepamem u pacienta s chronickou bolestí krční páteře a ramen
Keywords: baclofen; clonazepam; intoxication; seizures; coma; early recovery.; baklofen; clonazepam; intoxikace; záchvaty; koma; časná úprava stavu